Geophysical–Geochemical Reconstruction of Ancient Population Size – the Early Bronze Age Settlement of Fidvár (Slovakia). Issue 4 (15th September 2013) - Nowaczinski, Erich; Schukraft, Gerd; Rassmann, Knut; Hecht, Stefan; Texier, Fabienne; Eitel, Bernhard; Bubenzer, Olaf
ABSTRACT Population estimates are a vital backdrop to our understanding of ancient societies' socio‐economic structures and development. In order to facilitate such an informational mise en scène in terms of the early Bronze Age settlement of Fidvár in southwestern Slovakia, a new geophysical–geochemical approach is presented here, the first results of which are very promising. The crux of the new methodology utilizes the population's chemical fingerprint in relation to total anthropogenic phosphorus input as a proxy for different population models. These methods suggest an early Bronze Age population of 300–600 individuals, in accordance with the comparative analysis of a magnetic survey, and also matches initial archaeological estimates. Further methodological adjustments suggest an even higher population of up to 1000 inhabitants. In light of these figures, it is likely that Fidvár was one of the centres of the early Bronze Age socio‐economic system of the northern Pannonian Basin. Copyright © 2013 John Wiley & Sons, Ltd.